Prevalence and Risk Factors for Prolonged ICU Stay After Adult Cardiac Surgery - Mirinazhad, Mousa; Parsa, Dalir; Faridaalaee, Gholamreza; Bilehjani, Eissa; Irajian, Mohammad; Shadvar, Kamran; Naghipour, Bahman (Annals of Anesthesiology and Critical Care, 2016)
Background: The anticipation of the length of ICU stay would enable physicians to provide reliable information for better treatment methods. There are several risk factors for prolonged ICU stays after cardiac surgery in the related studies. Objectives: The aim of this study was to assess the possible factors contributing to the prolonged ICU stay in a referral heart center. Methods: In this retrospective case-control study, 515 adult patients admitted to ICU after cardiac surgery in Madani heart center in Tabriz (since March to September 2014) were divided into 2 short and prolonged ICU stay groups. ICU stays more than 3 days were considered prolonged. Various risk factors were compared between the two groups. Results: A total number of 64.9% of the patients were in the prolonged ICU stay group and 35.1% had a short stay. Among35 potential risk factors, some were significant factors affecting the length of ICU stay (age, type of surgery, previous cardiac surgery, a high dose of inotropes support, duration of surgery, length of CPB and aortic clamp time, arrhythmia in ICU, and re-operation). Conclusions: We can reduce ICU stay using the correction of high levels of serum creatinine before surgery, improvement of functional class with drug treatment, shortening of CPB and aortic cross clamp times, adequate hemostasis with surgeon and more correction of the coagulation status of the patient by the anesthesiologist at the end of the surgery.